The Link between Depression and Chronic Pain: Neural Mechanisms in the Brain - Cui, R.; Wang, Yicun; Liu, Shui; Sheng, Jiyao; Zhang, Xuewen (Journal of neural transplantation & plasticity, 2017)
Chronic pain, as a stress state, is one of the critical factors for determining depression, and their coexistence tends to further aggravate the severity of both disorders. Unfortunately, their association remains unclear, which creates a bottleneck problem for managing chronic pain-induced depression. In recent years, studies have found considerable overlaps between pain- and depression-induced neuroplasticity changes and neurobiological mechanism changes. Such overlaps are vital to facilitating the occurrence and development of chronic pain and chronic pain-induced depression. In this review, we summarized the role of neuroplasticity in the occurrence and development of the two disorders in question and explored individualized application strategies of analgesic drugs and antidepressants that have different pharmacological effects in the treatment of chronic pain-induced depression. Therefore, this review may provide new insights into the understanding of association between chronic pain and depression.